A systematic review for performance augmentation of solar still with heat storage materials: A state of art - Chauhan V.K.; Shukla S.K.; Rathore P.K.S. (My University, 2025)
Solar desalination is rising as the most prominent option to tackle water scarcity in every aspect of sustainable development. Much research has been done in the past that showed the continuous improvement in distilled water production from the solar desalination method. Although, solar desalination devices have gone through various kinds of modifications to make them more efficient and productive. Among them, solar heat storage techniques find their way to neutralize the sporadic nature of the sun and match the demand and supply requirements. The use of sensible and latent heat storage (LHS) materials with solar still (SS) has shown great response to ensures the incessant supply of freshwater. The sensible heat storage (SHS) materials are abundant in nature that makes them easy to access and affordable. Whereas, LHS material increases the nocturnal and cloudy time productivity. The use of biodegradable materials such as honey bee wax, cow dung, Gallus gallus domesticus cascara, and other biomass-derived material, as well as nonbiodegradable materials like plasmonic materials, multi PCM concept, an emulsion of PCM, and composite material and multi-dimensional heat storage concept have changed the scenario of heat storage capability and performance. This review consists of all the aforementioned concepts with detailed analysis in a combination of active and passive SS with SHS and LHS techniques. Additionally, coverage of the economic aspects of solar still equipped with thermal energy storage (TES) materials has also been included. © 2021 Elsevier Ltd